IMPULSIVE BUYING DIAGNOSIS AND TRIGGER FACTORS FOR ONLINE SHOPPING IN THE NEW NORMAL ERA - Edra Teaser Lukito; Pristiyono Pristiyono; Mulya Rafika; Yanto Zelibu (Journal of Applied Business Administration, 2022)
Changes in consumer behavior after Covid-19 and the new normal era in shopping are increasingly interesting to be discussed in depth by various academic researchers. The increase in impulsive buying that occurs in one period, especially online shopping is very good economically because it shows the high demand and supply will have an impact on the economy of a country. This study applies quantitative research to finding knowledge that uses data in the form of numbers as a tool to analyze information about what you want to know. The primary data collection technique was assisted by an online Google form with a simple random sampling technique with a sample size of 150 respondents. Statistical analysis used to test the hypothesis significantly uses the SmartPLS for students' application which includes testing the quality of the measurement model and testing hypotheses. It can be concluded that this study meets the requirements of construct reliability and validity, this is because all variables have Cronbach's alpha values and composite reliability values above 0.70 so they are declared reliable. The findings of this study indicate that website quality, flash sales, and shopping enjoyment are significant for impulsive buying online, and social influence is not significant for impulsive buying online. Meanwhile, the factors that trigger online shopping experienced by respondents of online shopping research have become a lifestyle, and have become a necessity of today's life.